2020
DOI: 10.1371/journal.pone.0235900
|View full text |Cite
|
Sign up to set email alerts
|

Impact of old age on the association between in-center extended-hours hemodialysis and mortality in patients on incident hemodialysis

Abstract: With the global problem of aging, it has become more difficult to improve the prognosis of older dialysis patients. Extended-hours hemodialysis offers longer treatment time compared to conventional hemodialysis regimen and provides favorable metabolic status, hemodynamic stability, and increased dietary intake. Despite prior studies reporting that in-center extended-hours hemodialysis can reduce the mortality rate, the treatment impact on elderly patients remains unclear. Therefore, we examined the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Recently, Hishida et al (2020) and Okazaki et al (2020) had demonstrated that extended-hours HD without dietary restrictions provided body weight increase, favorable metabolic status, hemodynamic stability, increased dietary intake and better survival rate, especially in elderly maintenance HD patients (more than 70 years old). However, they did not refer to the effects of extended-hours HD without dietary restrictions on the risk for developing of DRA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hishida et al (2020) and Okazaki et al (2020) had demonstrated that extended-hours HD without dietary restrictions provided body weight increase, favorable metabolic status, hemodynamic stability, increased dietary intake and better survival rate, especially in elderly maintenance HD patients (more than 70 years old). However, they did not refer to the effects of extended-hours HD without dietary restrictions on the risk for developing of DRA.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate energy and protein intake and exercise reduce the prevalence of sarcopenia (Sabatino et al 2021). A decreased risk of death in patients over 70 who received extended-hours hemodialysis without dietary restrictions has been reported (Okazaki et al 2020), suggesting that extended-hours hemodialysis without dietary restrictions may be an effective treatment option for elderly dialysis patients.…”
Section: Accepted Manuscript 13mentioning
confidence: 99%
“…Previous studies have shown that extended-hours HD is associated with lower mortality than conventional HD (typically three times per week, 3–5 hours per treatment) [ 18–21 ]. We have reported that extended-hours HD without strict dietary restriction, which we call a liberalized diet, was associated with improved survival compared with conventional HD, and that patients whose body mass index (BMI) was maintained or increased for 1 year after the induction of extended-hours HD had a better prognosis than those whose BMI decreased [ 22 , 23 ]. Although a previous study revealed that liberalized phosphorus intake among conventional HD patients was associated with better nutritional indicators and survival [ 24 ], clinicians often have difficulty balancing concerns about vascular calcification with phosphorus intake and dietary liberalization.…”
Section: Introductionmentioning
confidence: 99%